Perubahan Nilai Hematologi, Biokimia Darah, Bobot Organ dan Bobot Badan Tikus Putih pada Umur Berbeda (THE CHANGES ON HEMATOLOGICAL, BLOOD BIOCHEMICAL VALUES, ORGAN AND BODY WEIGHT OF RAT AT DIFFERENT AGES) - Sihombing, Marice; Tuminah, Sulistyowati (Jurnal Veteriner, 2012)
Research and development of health science require an animal model which has been known for itsorigin and characteristics. One of experimental animal model which is commonly used is albino rat. Thepurpose of this study was to investigate weight of organs (kidney, liver, spleen, and lung), hematologicalvalues (hemoglobin, hematocrit, erythrocyte and leucocyte), and the values of the biochemical blood (SGPT,SGOT, glucose and total protein) of the albino rat at different ages. This study used 60 rats, which weredivided into 3 groups based on age namely 1, 2, and 3 months and groups based on sex that each groupconsisted of 10 males and 10 females. Samples of age and sex groups of rat were taken randomly. Eachcage consisted of 5 rats with the same ages and sex. Those rats fed and tap water ad libitum. The rats weresacrificed anaesthetically by with ether to take their blood and measure their organ‘s weight. Data wasanalyzed using one way ANOVA test, except data from heart organ which was analyzed using nonparametrictest (Friedman Test). To find out the increase of rats body weight age 1 -3 months, it was usedregression linier test. Results of statistic showed that there were significantly difference (p < 0,05) in bodyweight change, average of hematological values, blood biochemical values and organs weight in accordancewith increasing of rats age in all age groups. In contrast, average of hematocrit values had no significantlydifference (p > 0,05). Generally, male rats were bigger than female rats but there was no difference in all
Keywords: Rattus norvegicus, body weight, hematological values, blood biochemical values